Expressions of vascular endothelial growth factor A, mucin-1, colony-stimulating factor-1, heparin-binding epidermal growth factor-like growth factor, and fibroblast growth factor 2 genes in the female reproductive tracts of women with ectopic pregnancy: A case-control study - Sima Golkar; Zahra Chekini; Fatemehsadat Amjadi; Parvaneh Afsharian; Aida Najafian; Firouzeh Ghaffari; Reza Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Ectopic pregnancy (EP) is defined as embryo implantation in a location other than the uterine cavity. Objective: We aimed to evaluate the expression of several genes, which may play a role in EP, in the ampulla region of fallopian tubes and endometrial tissue of women with EP. Materials and Methods: In this case-control study, 5 women who underwent salpingectomy due to EP, comprised the 5 pseudo-pregnant women as a control group. These participants referred to the Royan Institute, Shariati, and Arash hospital, Tehran, Iran during 2019-2021. We evaluated the expressions of vascular endothelial growth factor A, mucin-1, colony-stimulating factor-1, heparin-binding epidermal growth factor-like growth factor (HBEGF), and fibroblast growth factor 2 genes in the fallopian tube and endometrium of EP cases by real-time polymerase chain reaction using specific primers. Results: The vascular endothelial growth factor expression was significantly higher in the ampulla region of the controls. However, no significant differences were observed in endometrial tissue. Assessments of colony-stimulating factor-1 and fibroblast growth factor 2 showed no significant differences between the case and control groups. HBEGF showed significantly higher expression in the ampulla region of EP cases, but no significant difference was observed in HBEGF expression in the endometrial tissues of the study groups. Mucin-1expression was significantly higher in both study regions of the EP cases. Conclusion: Our results have strongly suggested that these genes play important roles in proper implantation, and disruptions in their expression patterns could lead to EP. However, more studies are needed to confirm the current findings.